STUDI PENAMBAHAN AIR KELAPA PADA PEMBUATAN PUPUK CAIR DARI LIMBAH CAIR IKAN TERHADAP KANDUNGAN HARA MAKRO C, N, P, DAN K - Yovina Mulyadi; Sudarno Sudarno; Endro Sutrisno (Jurnal Teknik Lingkungan, 2013)
Liquid fertilizer content from fish wastewater had not fulfill the requirement of Agriculture Minister rules No.70/Permentan/SR.140/10/2011 with C-organic content 15.42%, Total N 1.26%, Phosphate 4.37%, and Potassium 0.36% thus variated coconut water for the enrichment of Total N and Potassium content. Liquid fertilizer made from fish wastewater is made by mixing fish wastewater, rice wash water, molasses, and coconut water (with variation of 0, 100, 200, 300, 400, and 500 ml) into the reactor and anaerobically fermented during 20 days then do the measurement of pH and Temperature every day and content of CNPK(C-Organic, N Total, Phosphate, and Potassium) on day 0, 10th, and 20th. The optimum result that is obtained from the measurement of  liquid fertilizer content from fish wastewater on day 10 with the variation of 500 ml of coconut water with content of C-Organic 17.12%, Total N 3.09%, 0.41% Phosphate, and 0.0066% Potassium.